A Statewide Analysis of the Incidence and Outcomes of Acute Mesenteric Ischemia in Maryland from 2009 – 2013. - Robert Stuart Crawford; Donald Gilbert Harris; Elena eKlyushnenkova; Ronald B Tesoriero; Joseph eRabin; Hegang eChen; Jose J Diaz (Frontiers in Surgery, 2016)
Introduction.Acute mesenteric ischemia is a surgical emergency that entails complex, multi-modal management, but its epidemiology and outcomes remain poorly defined. The aim of this study was to perform a population analysis of the contemporary incidence and outcomes of mesenteric ischemia.Methods.This was a retrospective analysis of acute mesenteric ischemia in the state of Maryland during 2009 – 2013 using a comprehensive statewide hospital admission database. Demographics, illness severity, comorbidities, and outcomes were studied. The primary outcome was inpatient mortality. Survivors and non-survivors were compared using univariate analyses, and multivariable logistic regression analysis was performed to evaluate risk factors for mortality.Results.During the 5-year study period, there were 3,157,499 adult hospital admissions in Maryland. 2,255 patients (0.07%) had acute mesenteric ischemia, yielding an annual admission rate of 10/100,000. Increasing age, hypercoagulability, cardiac dysrhythmia, renal insufficiency, increasing illness severity, and tertiary hospital admission were associated with development of mesenteric ischemia. Inpatient mortality was high (24%). After multivariate analysis, independent risk factors for death were age > 65 years, critical illness severity, mechanical ventilation, tertiary hospital admission, hypercoagulability, renal insufficiency, and dysrhythmia.Conclusions.Acute mesenteric ischemia occurs in approximately 1/1000 admissions in Maryland. Patients with mesenteric ischemia have significant illness severity, substantial rates of organ dysfunction, and high mortality. Patients with chronic comorbidities and acute organ dysfunction are at increased risk of death, and recognition of these risk factors may enable prevention or earlier control of mesenteric ischemia in high-risk patients.